DAMPAK SERVICE ENCOUNTER QUALITY TERHADAP SERVICE VALUE EVALUATION: STUDI PADA HIGHER EDUCATION SERVICE - Fatik Rahayu (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
This paper aims to examine the impact of service encounter quality on service value evaluation within a higher education context, especially in class learning process. Service encounter quality was approached with three dimensions, they are : instructor interaction competencies, instructor task competencies and student interaction competencies. Service value evaluation in this study was called as learning experience value. Some qustionares were distributed to 306 students in some classes. The data were analysed with multiple regression. The result showed there are significant impacst of the three dimensions of service encounter quality on the learning experience value.